Timely Follow-Up of Abnormal Diagnostic Imaging Test Results in an Outpatient Setting: Are Electronic Medical Records Achieving Their Potential? - Singh, Hardeep (2009)
BACKGROUND: Given the fragmentation of outpatient care, timely follow-up of abnormal diagnostic test results remains a challenge. We hypothesized that an EMR that facilitates the transmission and availability of critical imaging results through either automated notification (alerting) or direct access to the primary report would eliminate this problem. METHODS: We studied critical imaging alert notifications in the outpatient setting of a tertiary care VA facility from November 2007 to June 2008. Tracking software determined whether the alert was acknowledged (i.e. provider opened the message for viewing) within two weeks of transmission; acknowledged alerts were considered read. We reviewed medical records and contacted providers to determine timely follow-up actions (e.g. ordering a follow-up test or consultation) within 4 weeks of transmission. Multivariable logistic regression models accounting for clustering effect by providers analyzed predictors for two outcomes; lack of acknowledgment and lack of timely follow-up. RESULTS: Of 123,638 studies (including X-rays, CT scans, ultrasounds, MRI and mammography), 1196 (0.97%) images generated alerts; 217 (18.1%) of these were unacknowledged. Alerts had a higher risk of being unacknowledged when ordering providers were trainees (OR, 5.58;95%CI, 2.86-10.89) and when dual (more than one provider alerted) as opposed to single communication was used (OR, 2.02;95%CI, 1.22-3.36). Timely follow-up was lacking in 92 (7.7% of all alerts) and was similar for acknowledged and unacknowledged alerts (7.3% vs. 9.7%;p=0.2). Risk for lack of timely follow-up was higher with dual communication (OR,1.99;95%CI, 1.06-3.48) but lower when additional verbal communication was used by the radiologist (OR, 0.12;95%CI: 0.04-0.38). Nearly all abnormal results lacking timely follow-up at 4 weeks were eventually found to have measurable clinical impact in terms of further diagnostic testing or treatment. CONCLUSIONS: Critical imaging results may not receive timely follow-up actions even when providers receive and read results in an advanced, integrated EMR system. A multidisciplinary approach is needed to improve patient safety in this area.